Antagonist co-activation during short and medium latency responses in subjects with chronic ankle instability - Pinheiro De Sousa, Andreia Sofia (2020)
This study aims to evaluate bilateral ankle antagonist co-activation during compensatory postural responses, including short latency responses (SLR) and medium latency responses (MLR), in response to a unilateral sudden ankle inversion in subjects with chronic ankle instability (CAI). Methods Twenty-four participants with CAI and 20 controls participated in the present study. Bilateral eletromyography of peroneus longus (PL), peroneus brevis (PB), tibialis anterior (TA) and soleus (SOL) muscles was collected during a unilateral sudden inversion perturbation (30°) to assess antagonist co-activation of SOL/TA and TA/P pairs during SLR and MLR in both support and perturbed positions. Results Compared to control group, participants with CAI presented: (1) bilateral increased antagonist co-activation of SOL/TA MLR in the support position; and (2) decreased antagonist co-activation of TA/P MLR of uninjured limb in the support position and of injured limb in the perturbed position. Conclusions CAI involves deregulation of ankle antagonist co-activation of MLR in both injured and uninjured limbs.